RIWAYAT BERAT BADAN LAHIR RENDAH DAN IMUNISASI SEBAGAI PREDIKTOR STUNTING PADA BALITA USIA 24-59 BULAN - Kamrin, Kamrin; Irma, Irma (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The prevalence of stunting in Indonesia remains quite high, and this issue has occurred in various districts and cities across the country. This study aims to identify predictors of stunting occurrence in children aged 24-59 months. This research is an observational analytical study with a case-control design. The predictor variables in this study are the history of low birth weight (LBW) and immunization history, while the effect variable is the incidence of stunting. The population and sample for this study are children aged 24-59 months living in the working area of the Wakorumba Utara Health Center, selected using non-random sampling techniques, totaling 150 respondents with a case-to-control ratio of 1:1 (75 case samples and 75 control samples). A questionnaire was used as a tool for data collection, and the collected data were analyzed univariately and bivariately using the chi-square statistical test (α=0.05). The data analysis results indicated a p-value of 0.002 and an odds ratio (OR) of 2.989 (1.537-5.812) for the effect of LBW history on the incidence of stunting, and a p-value of 0.276 and an OR of 0.315 (0.61-1.614) for the effect of immunization history on the incidence of stunting. The findings of this study conclude that a history of LBW is a predictive factor for the occurrence of stunting in children aged 24-59 months in the working area of the Wakorumba Utara Health Center, while a complete basic immunization history is a protective factor against stunting in the same age group. It is recommended that ANC services and education about the importance of complete basic immunization for children and efforts to prevent stunting be continuously improved by health center staff.